Small & Scary - BENTON, Michael (Discovering Dinosaurs, 2015)
Some dinosaurs were small as a cat. How did they live alongside big monsters such as Tyrannosaurus res? What did they eat and how did they defend themselves? Explore these question and more about the most cunning little creatures of the dinosaur age.